A systematic review of prospective epidemiological research into injury and illness in Olympic combat sport - Bromley, S. J.; Drew, M. K.; Talpey, S.; McIntosh, A. S.; Finch, C. F. (British Journal of Sports Medicine, 2018)
Background Combat sports involve body contact through striking, kicking and/or throwing. They are anecdotally referred to as `dangerous`, yet long-term investigation into specific injury rates is yet to be explored.